Study of the road surface properties that control the acoustic performance of a rubberised asphalt mixture. (15th January 2016) - Vázquez, V.F.; Paje, S.E.
Graphical abstract: Highlights: A test track constructed with and without crumb tire rubber was assessed. A high content of crumb rubber was added to the mixture by wet process. Dynamic stiffness of the mixtures was measured in in - situ conditions. Dynamic stiffness influence on tyre/pavement noise is not significant. Abstract: Simultaneously with the fact that vehicle industry has been able to lower the noise emission from driving vehicles, tire/pavement noise has become the most significant source of traffic noise. In order to reduce it, low noise surfaces are seen as a practical solution. One of these types of surfaces may be elaborated with bituminous mixtures with crumb tire rubber added to the binder in high content by a wet process. However, the generation mechanisms involved in the tire/pavement sound and the reasons of the noise attenuation achieved with these mixtures are not so clear. This study analyses the different generation mechanisms that take place in the tire/pavement sound generation in these crumb tire rubber pavements. The surface properties of the in-service pavement, which are most important in controlling the acoustic performance (texture, acoustic absorption and dynamic stiffness or mechanical impedance), have been measured for the characterization of a test track constructed with and without crumb tire rubber. After results correlation of these surface characteristics in a pavement with crumb tire rubber added by a wet process, it seems that the parameters of roughness and texture could have a relevant role in the global tire/pavement sound emission, whereas dynamic stiffness influence is relatively minor.